2004
DOI: 10.1073/pnas.0304068101
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of an extreme sex-ratio bias in a natural population

Abstract: The sex ratio is a key parameter in the evolution and ecology of a species. Selfish genetic elements that bias the sex ratio of affected individuals are well known and characterized, but their effect on populations has been considered limited, because either the element does not achieve high prevalence or the host rapidly evolves resistance to the distorting element, reducing its prevalence. We tested whether the host necessarily prevails by using a butterfly system where records from the early part of the 20t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
187
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(190 citation statements)
references
References 25 publications
0
187
2
1
Order By: Relevance
“…To answer this question, they compare their results with other island with lower Wolbachia infection in H. bolina. They interpret that low male frequency leads to 57 % loss of reproductive output [41]. They further found that male spermatophores of H. bolina from Independent Samoa were almost half the diameter of spermatophores produce by H. bolina from neighboring island.…”
Section: Wolbachia Diversity In the Butterfliesmentioning
confidence: 92%
See 1 more Smart Citation
“…To answer this question, they compare their results with other island with lower Wolbachia infection in H. bolina. They interpret that low male frequency leads to 57 % loss of reproductive output [41]. They further found that male spermatophores of H. bolina from Independent Samoa were almost half the diameter of spermatophores produce by H. bolina from neighboring island.…”
Section: Wolbachia Diversity In the Butterfliesmentioning
confidence: 92%
“…In 2004, Dyson and Hurst [41] had shown that this extreme sex bias is persistent at least 400 generation after its first record in Independent (Western) Samoa. They further concluded that, sex bias is because of high prevalence of MK Wolbachia and not because of parthenogenesis.…”
Section: Wolbachia Diversity In the Butterfliesmentioning
confidence: 99%
“…uninfected females and infected males), but solely linked to the magnitude of the fertility reduction of male carriers. In Hypolimnas bolina butterflies for example, many South Pacific populations harbour a male-killing strain of Wolbachia [65]. Intriguingly, different populations have different frequency of male killers that is associated with differences in degree of female-biased sex ratio, with a higher frequency of male killers associated with a more severely female-biased population sex ratio [66].…”
Section: Do Selfish Genetic Elements Promote Polyandry?mentioning
confidence: 99%
“…Lepidoptera have proven an excellent group for exploring arthropodendosymbiont dynamics (Dyson and Hurst, 2004;Hornett et al, 2006;Sugimoto and Ishikawa, 2012). This group harbors bacterial symbionts such as Spiroplasma and Wolbachia collectively known to impose CI, male killing and feminization (Jiggins et al, 2000;Hiroki et al, 2004;Charlat et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This group harbors bacterial symbionts such as Spiroplasma and Wolbachia collectively known to impose CI, male killing and feminization (Jiggins et al, 2000;Hiroki et al, 2004;Charlat et al, 2005). Studies of butterfly male-killing have yielded valuable insights into host-symbiont coadaptation, including the genetic and biogeographic basis of nuclear host suppression (Dyson and Hurst, 2004;Hornett et al, 2006Hornett et al, , 2008Charlat et al, 2007b, c). Lepidopterans have also informed the study of feminization, primarily via the work in Wolbachia-infected Ostrinia moths (Crambidae) and Eurema butterflies (Pieridae).…”
Section: Introductionmentioning
confidence: 99%